The utility of handheld ultrasound as a point-of-care screening tool to assess vocal fold impairment following congenital heart surgery. (September 2021) - Deshpande, Anita; Tey, Ching Siong; Chanani, Nikhil; Landry, April; Raymond, Mallory; Sebelik, Merry; Shashidharan, Subhadra; Wolf, Michael; Raol, Nikhila
Abstract: Introduction: Vocal fold motion impairment (VFMI) is a known potential complication of congenital heart surgery (CHS). Flexible nasolaryngoscopy (FNL) is the gold standard for evaluation of vocal fold movement but has risks, including epistaxis, desaturation, and changes in heart rate. Laryngeal ultrasound (LUS) has begun to emerge as a diagnostic tool and has been shown to have high accuracy in the evaluation of VFMI. We sought to assess the utility of hand-held LUS as a point-of-care screening tool to assess VFMI in pediatric patients following congenital heart surgery. Methods: Using a prospective cohort design, children under 18 years who were undergoing congenital heart surgery at a tertiary care pediatric hospital were enrolled. All patients underwent postoperative LUS and FNL. All studies were reviewed by two otolaryngology reviewers blinded to the clinical diagnosis. Higher quality studies were reviewed by two cardiology reviewers also blinded to the clinical diagnosis. Accuracy and inter-rater reliability were calculated. Results: Sixty-two children were screened. Fourteen children with VFMI were identified via FNL. When comparing LUS and FNL, both individual accuracy (90.3% and 75.8%) and interrater agreement (79% overall, 96% for high quality videos) were high for the otolaryngology reviewers. The cardiology reviewers were able to obtain 100% accuracy for high quality videos. Conclusion: Handheld LUS has utility as a point-of-care screening tool to assess VFMI. This may have benefit in low-resource settings, for universal screening in cardiac intensive care units, or in settings where otolaryngology consultation may be difficult to obtain.